2004
DOI: 10.1038/sj.ijo.0802527
|View full text |Cite
|
Sign up to set email alerts
|

Thermogenesis and weight loss in obese individuals: a primary association with organochlorine pollution

Abstract: The main objective of this study was to investigate the potential impact of body organochlorine (OC) pollution on the adaptive change in thermogenesis induced by body weight loss. Fat mass (FM), fat-free mass (FFM), and sleeping metabolic rate (SMR) were measured in obese individuals before and after a weight-reducing program. The measured values of SMR were then compared to those predicted from a reference equation established from FM and FFM in control subjects. Plasma OC, leptin, total tri-iodothyronine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 14 publications
3
47
0
1
Order By: Relevance
“…Indeed, in the context of a 15-week weight reduction program, an increase in plasma organochlorine concentration has successively been shown to be the best predictor of the significant decrease in resting metabolic rate 61 and of the significant greater than predicted decrease in sleeping EE, 12 explaining 32 and 47% of these variables, respectively (see Table 3). Interestingly, in this last study, 12 this corresponded to a greater percentage than what change in plasma leptin concentration (20%) and plasma leptin concentration after weight loss (13%) did explain. These relationships are surprising but could nevertheless be explained, at least partly, through the relation between plasma organochlorine concentration and lowered plasmafree thyroxine and total thyroxine levels that have been reported in several human studies.…”
Section: Organochlorines: Obesogen Pollutants?mentioning
confidence: 54%
See 1 more Smart Citation
“…Indeed, in the context of a 15-week weight reduction program, an increase in plasma organochlorine concentration has successively been shown to be the best predictor of the significant decrease in resting metabolic rate 61 and of the significant greater than predicted decrease in sleeping EE, 12 explaining 32 and 47% of these variables, respectively (see Table 3). Interestingly, in this last study, 12 this corresponded to a greater percentage than what change in plasma leptin concentration (20%) and plasma leptin concentration after weight loss (13%) did explain. These relationships are surprising but could nevertheless be explained, at least partly, through the relation between plasma organochlorine concentration and lowered plasmafree thyroxine and total thyroxine levels that have been reported in several human studies.…”
Section: Organochlorines: Obesogen Pollutants?mentioning
confidence: 54%
“…Indeed, it has been well demonstrated that the decrease in EE during energy restriction and weight loss programs can be greater than expected from the decrease in fat mass and fat-free mass, [3][4][5] despite these two variables accounting for over 82% of the variance in EE. [6][7][8][9][10] This paper thus specifically focuses on an adaptive reduction in EE in response to energy restriction that can be observed in any component of total EE, 3,4,11,12 traditionally divided into resting and non-resting EEs (including physical activity and non-exercise activity EEs), and thermic effect of food.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, Yudkin et al 6 suggested that similar inflammatory mediators may be a link connecting obesity and coronary heart disease. The suggestion that environmental pollutants may be a risk factor for obesity has gained support from the results of another recent study by Tremblay et al 7 In a 15-week weightloss program of 15 obese subjects and 86 nonobese controls, they showed that the obese group had lost on average a little more than 10 kg, and that, as a group, their metabolic rate had decreased by approximately 12%. In a multiple regression analysis, total plasma organochlorine (OC) concentration was the factor explaining the greatest proportion of the difference between predicted and measured metabolic rate changes during sleep induced by body weight loss.…”
Section: Introductionmentioning
confidence: 64%
“…It could also be defined as a non-obligatory thermogenesis which is affected by some hormones and neurosystems as well as by some environmental factors such as pollution. 17 In this regard, the main factor of this study is OSAS which is also susceptible to influence this adaptive component of energy expenditure. We hypothesized that an hypoxic stress that is sufficiently severe may promote a decreased adaptive thermogenesis in apneic patients.…”
Section: Introductionmentioning
confidence: 99%